NEW DXA DIAGNOSTIC INDEXES OF ABDOMINAL OBESITY - Shubeska Stratrova, Slavica; Jovanovska Mishevska, Sasha; Efremovska, LJudmila; Bitoska, Iskra; Spasovski, Dejan (Macedonian Academy of sciences and Arts, 2021)
Aim: Cushing’s syndrome (CS) is associated with weight gain and extreme central, visceral, abdominal obesity which is confirmed with dual-energy X-rays absorptiometric (DXA) diagnostic cut-off point (CP) values of central obesity indexes (COI), determined as an android to gynoid tissue and fat mass ratios. These best differentiate CS from non-CS obese women matched with CS according to their age and BMI. The aim of this study was to determine the CP values of new DXA indexes of central, abdominal obesity as a ratio of android and trunk to legs as well as trunk and legs to total tissue and fat mass that best differentiate CS and matched non-CS obese women in order to confirm central abdominal obesity, and to determine their normal CP values that best differentiate healthy non-obese women from CS and non-CS obese women, and to exclude abdominal obesity completely. Material and Methods: DXA indexes of abdominal obesity, calculated as а ratio of regional body fat and tissue mass compartments android to legs (A/L), trunk to legs (Tr/L), trunk to total (Tr/To) and legs to total (L/To) values were determined among 4 groups. Each group consisted of 18 women: 1st group of CS, 2nd group of obese women (O1) not different according to their age and BMI from CS, 3rd group of obese women (O2) with higher BMI of 35 ± 1.2 kg and a 4th group of non-obese, healthy women (C) with a normal BMI. Diagnostic accuracy (DG) of CP values of DXA indexes of abdominal obesity and indexes of normal body fat distribution (BFD) were determined. Results: A/L, Tr/L, Tr/To, and L/To DXA indexes were significantly different between CS and O1 as well as between non-CS women O2 compared to O1 and C. These indexes had a highly significant correlation among each other and also in relation to their BMI (p < 0.0001). A/L-Tm CP value of 0.3 best differentiated the CS from group O1, with the highest DG of 100 % and an A/L-Fm CP value of 0.26 differentiated them with a DG of 94.44% and sensitivity of 100 %. An A/L-Tn CP value of 0.23 and an A/L-Fn CP value of 0.25 best differentiated CS and C as well as O2 and C for the highest DG of 100 %. Conclusions: DXA indexes A/L, Tr/L, Tr/To and L/To values were significantly different among the four groups. These values correlated significantly among them and with their BMI in non-CS groups, thus confirming a BMI increase association with a more pronounced abdominal BFD. An A/L-Tm CP value of 0.3 and an A/L-Fm CP value of 0.26 were discovered as the best DXA diagnostic indexes of extreme abdominal obesity in CS and these could also be used in discovering abdominal BFD in non-CS obese women with metabolic syndrome (MS). An A/L-Tn CP value of 0.23 and an A/L-Fn CP value of 0.25 were discovered as the best DXA diagnostic indexes of normal BFD which completely excluded abdominal obesity.
Keywords: DXA; abdominal obesity; DXA obesity indexes; cut-off point values